2018
DOI: 10.1016/j.amepre.2018.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Eating, Activity, and Weight-related Problems From Adolescence to Adulthood

Abstract: The majority of young people have some type of eating, activity, or weight-related problem at all stages from adolescence to adulthood. Findings indicate a need for wide-reaching interventions that address a broad spectrum of eating, activity, and weight-related problems prior to and throughout this developmental period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
82
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 62 publications
3
82
0
5
Order By: Relevance
“…Body image concerns and disordered eating are major health problems that persist from a young age into adulthood [1]. Research suggests that sociocultural pressures lead to the internalization of the thin and/or muscular/athletic body ideal and social comparisons [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body image concerns and disordered eating are major health problems that persist from a young age into adulthood [1]. Research suggests that sociocultural pressures lead to the internalization of the thin and/or muscular/athletic body ideal and social comparisons [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Failing to adjust to a socially stereotyped body image leads to body dissatisfaction in men and women [2]. In turn, body dissatisfaction is associated with disordered eating [1]. Body image concerns and eating pathology are associated with lower psychosocial functioning and an unhealthy lifestyle in young adults [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Body image concerns and disordered eating are major health problems in youth (Neumark‐Sztainer et al, ). The most reliable method for diagnosing and assessing eating disorders (EDs) is a structured or semistructured clinical interview administered by trained clinicians (Fairburn & Beglin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Body image concerns and body dissatisfaction are highly prevalent in adolescents worldwide [1][2][3][4][5]. Studies have demonstrated that adolescents' body image concerns are associated with disturbed eating attitudes and behaviors (DEABs) that might be the precursor of clinical eating disorders [6,7].…”
Section: Introductionmentioning
confidence: 99%